2018
DOI: 10.1177/8755122518755402
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Pharmacotherapy Management of Urinary Tract Infections in Pediatric Patients

Abstract: To discuss the risk factors, microbial resistance rates, and pharmacotherapy, including antimicrobial choices and medication dosage regimens, for urinary tract infections (UTIs) in pediatric patients. Data Sources: A MEDLINE literature search (1985 to December 2017) was performed using the following keywords and associated medical subject headings: urinary tract infection, antimicrobial, treatment, and children. Study Selection and Data Extraction: Search was conducted to identify clinical trials, systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 177 publications
1
7
0
Order By: Relevance
“…30 However, this still requires further research in the form of randomized controlled trials (RCT). 31 This study showed that the five most common gramnegative bacteria were sensitive to carbapenems (imipenem, meropenem), amikacin, and piperacillin-tazobactam, similar to Rahmadi in his research on UTI patients at the Department of Internal Medicine Dr. Soetomo Hospital. 32 In Taiwan, Wu et al reported that E. coli was resistant to ampicillin, piperacillin, trimethoprim-sulfamethoxazole, and sensitive to amikacin, imipenem, ceftazidime, ceftriaxone, and cefuroxime, gentamicin.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…30 However, this still requires further research in the form of randomized controlled trials (RCT). 31 This study showed that the five most common gramnegative bacteria were sensitive to carbapenems (imipenem, meropenem), amikacin, and piperacillin-tazobactam, similar to Rahmadi in his research on UTI patients at the Department of Internal Medicine Dr. Soetomo Hospital. 32 In Taiwan, Wu et al reported that E. coli was resistant to ampicillin, piperacillin, trimethoprim-sulfamethoxazole, and sensitive to amikacin, imipenem, ceftazidime, ceftriaxone, and cefuroxime, gentamicin.…”
Section: Discussionsupporting
confidence: 73%
“…14 The increasing resistance of trimethoprim-sulfamethoxazole in various regions has resulted in this antibiotic being no longer recommended as empiric therapy unless it is proven to be sensitive according to local antibiogram data. 31 Meanwhile, cefoperazonesulbactam showed a sensitivity of more than 90% in ESBL-producing Enterobacteriaceae. 34 Tigecycline is well tolerated in cases of serious Extensively Drug-Resistant (XDR) gramnegative bacterial infections 35 , but should not be used as monotherapy in pediatric UTIs because of its limited excretion and some side effects, enamel hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Cefuroxime exhibits a broad spectrum of activity against Gram-negative and Gram-positive bacteria [1]. The main indications include respiratory tract infections, middle ear infections, sinus infections caused by non-β-lactamase-producing strains, and treatment of urinary tract infections also of pediatric patients [2,3]. Esterification of cefuroxime into the prodrug form facilitated its permeation, resulting in increased bioavailability, and enabled the development of oral formulations [4].…”
Section: Introductionmentioning
confidence: 99%
“…Females and uncircumcised males 5,20 had a higher rate of UTIs. 21 About a third of all women had a contaminated UC, but only 6% had an antibiotic change and none had antibiotic discontinuation. Patients with a contaminated UC did not have a repeat culture performed to confirm a UTI diagnosis.…”
Section: Discussionmentioning
confidence: 99%